Improving Learning Outcomes on History of World War II Material Through the Application of the Problem-Based Learning Model for Class XII-2 Students at SMA Negeri 5 Medan - Apriyana, Roro Ajeng; Nasution, Abd Haris; Nasution, Sovianur (CV. Rayyan Dwi Bharata, 2024)
This research aims to measure how effective the problem-based learning model is in increasing the understanding of class XII-2 students at SMA Negeri 5 Medan regarding World War II. Using the Classroom Action Research (PTK) method in two cycles, this research involved learning results tests and observations to collect data. The results of research using a problem-based learning model in class XII-2 students at SMA Negeri 5 Medan showed a significant increase in learning outcomes for World War II material. This is evidenced by the increase in the average student test score from 78 in the first cycle to 82 in the second cycle. Apart from that, observations also show an increase in student learning activities, such as group discussions and information seeking.